Barbados : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in Barbados during the 1990s. Economic activity declined during 1990-92 but began to recover in 1993. The recovery started slowly in 1993, but picked up in 1994, and real GDP grew by 3.8 percent in that year. Adverse weather in 1994 led to a drop in sugar output in 1995 and a deceleration in the growth rate of the economy to 2.9 percent. As sugar production reverted to normal levels, real GDP growth reached 5.2 percent in 1996.